Sequential analysis to identify Non-Steroid Anti-Inflammatory (NSAID) with colorimetric amd microcrystallization reactions - Saavedra, Félix (2019)
Given the constant presence of fraudulent drugs in unauthorized sales places, it is necessary to have simple methods to identify the active ingredients, for this purpose, a sequential analytical method is proposed to identify NSAIDs, which consists of three stages: drop test , reactions in tube with aqueous solution 0.1% of diclofenac sodium, naproxen sodium and ibuprofen and reaction separately with aqueous solutions of 0.1N AgNO3, 0.5N CuSO4 and 0.1N FeCl3 originating in each case, after 2-3 minutes , opalescence and characteristic color similar for both the secondary standard and the solution analyzed. In the third stage, said NSAIDs in aqueous medium at concentration 75mg / 5mL separately, was added 4 drops of the reagent obtained by interaction of cobalt nitrate and ammonium thiocyanate originating microcrystals whose geometric structure was observed under optical microscope at 40x; specifically, when this reaction was carried out with the ampoule content of diclofenac (75mg / 3mL), coming from different countries, after two three minutes, in the test tube abundance of microcrystals was observed, being established that the additives and Preservatives do not interfere with the reaction. Similarly, diclofenac sodium tablets (50 mg) were analyzed. It is concluded that three of the four NSAIDs analyzed, diclofenac sodium, naproxen sodium and ibuprofen can be identified both in the pure state (secondary standards) and in their pharmaceutical presentations -tablets and ampoules-, by the similarity of the results obtained in the three stages successive proposals.